Synthesis, characterization and investigation of electrochemical and spectroelectrochemical properties of non-peripherally tetra-5-methyl-1,3,4-thiadiazole substituted copper(II) iron(II) and oxo-titanium (IV) phthalocyanines - KOCA, ATIF (ELSEVIER, 2017)
In this study novel substituted phthalonitrile (3) and non-peripherally tetra 5-Methyl-1,3,4-thiadiazole substituted copper(II) (4), iron(II) (5) and oxo-titanium (IV) (6) phthalocyanines were synthesized. These novel compounds were fully characterized by FT-IR, H-1 NMR, UV-vis and MALDI-TOF mass spectroscopic techniques. Voltammetric and in situ spectroelectrochemical measurements were performed for metallo-phthalocyanines (4-6). Ti(Iv)0Pc and (FePc)-Pc-II showed metal-based and ligand-based electron transfer reactions while (CuPc)-Pc-II shows only ligand-based electron transfer reaction. Voltammetric measurements indicated that the complexes have reversible, diffusion controlled and one electron redox reactions. The assignments of the redox processes and color of the electrogenerated species of the complexes were determined with in-situ spectroelectrochemical and electrocolorimetric measurements. These measurements showed that the complexes can be used as the electrochromic materials for various display technologies. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Thiadiazole; Electrochemistry; Spectroelectrochemistry; METAL-FREE; COBALT; COMPLEXES; MANGANESE; NICKEL; BULKY; FILMS